EVALUASI DAMPAK KEBIJAKAN REKLAMASI PANTAI DI TELUK LAMPUNG (Studi Dampak Sosial-Ekonomi Nelayan Kelurahan Sukaraja Pada Kasus Reklamasi Pantai Di Kelurahan Bumi Waras, Kecamatan Bumi Waras, Kota Bandar Lampung) - administratio Department; Fitri Wahyuni; Meiliyana Meiliyana (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2017)
ABSTRACT. The policy of coastal reclamation in the Teluk Lampung ample posessome problems or lack of socio-economic conditions of rendering of fishermenaround the area of reclamation. After the policy of coastal reclamationimplemented, have are gave an impact on the fishermen about being the difficulty in finding fish and meet his needs. So the formula obtained by the issue of howsocio-economic impacts of fishing due to the perceived policy of coastalreclamation in the Teluk Lampung, especially Kelurahan Sukaraja. The purpose ofthis research is to give an overview of the impact of the social economy isperceived as one of the fishermen the impact arising from the existence of apolicy of coastal reclamation in the Teluk Lampung. This research was conductedto evaluate the impact of coastal reclamation policy. In evaluating the impact ofthis policy, researchers used the theory of impact evaluations or evaluationsummative evaluation methods belonged to Rossi and Freeman, then use the lawand some other supporting theory. Type of this research is descriptive researchwith qualitative approach. Conclusion of this research is the policy of coastalreclamation have yet to produce the desired impact. This is due to several factors.(1) Problems related to lack of public land in the town of Bandar Lampung has yetto be resolved, (2) the lack of participation or the participation of coastalcommunities, (3) how implementation is not appropriate, (4) the Government ofthe city of Bandar Lampung that have yet to implement environmentallydevelopment, (5) Yet the existence of the handling of the Government of the cityof Bandar Lampung accepted impact-related coastal communities, (6) theincidence of coastal communities must feel aggrieved and only benefit thedeveloper. In addition, the policy of reclaiming the beaches generate unwantedimpacts for coastal communities in particular Kelurahan Sukaraja fisherman. Sothe Government of the city of Bandar Lampung need to apply environmentallydevelopment, oversight and coordination to deal with the impact of requiringcommunity as well as in the process of coastal reclamation policy. Keywords: Policy, Evaluation, Coastal Reclamation, Impact.